Model Pembelajaran Berbasis Proyek pada Mata Kuliah Praktik Kewirausahaan Untuk Menunjang Kemampuan Mahasiswa dalam Melakukan Promosi, Publishing dan Penjualan Produk Hasil Praktik Kuliah - Muhamad Ridwan; Nova Darmanto; Dadang Syaputra (Politeknik Negeri Media Kreatif, 2022)
This study aims to examine how the implementation of a project-based learning model is applied to a practical course at Polimedia Kreatif to design student self-employment in entrepreneurship. This study uses the classroom behavioral research method. This study presents data, facts, and circumstances arising in this area. The subjects of this survey are students of her Polimedia Kreatif Culinary Arts course in the 4th semester of 2022. The means used in the study were performing tasks, conducting business consultations, presenting products, and reporting evaluation results. Data from observations were analyzed using qualitative descriptive techniques. The results of the study concluded that the successful application of project-based learning models in entrepreneurship courses to promote student independence in the field of entrepreneurship was declared successful. In summary, her three measures of success in this study are task completion, report activity, and report writing.